Comportamento fiscal e cidades inteligentes: efeitos da nota fiscal de serviços eletrônica em municípios brasileiros - Batista, Elaine Assunção (2024)
Smart cities use digital and communication technologies to improve the quality of life of their inhabitants, improve the efficiency of urban services and infrastructures and promote sustainability (Almada, 2022). Due to their advanced information technology infrastructure, these cities offer an enabling environment to make tax management more efficient, transparent and simplified. From this, the concept of electronic governance gains relevance, as it refers to the use of technology to improve public services and encourage citizen participation. The general objective of the study is to evaluate the infrastructure system in Information and Communication Technologies (ICTs) in the context of tax administration, as an electronic governance instrument in smart cities, focusing on the impact of the Electronic Services Invoice on the tax efficiency and the quality of public spending. The central hypothesis of this study is that the implementation of technologies in municipal tax administrations can increase local revenue collection and improve the quality of public spending, by reducing tax evasion and increasing transparency, strengthening social control. To this end, data on municipal revenue and expenditure were collected, and it was determined whether or not the city had implemented an NFSe issuance system. Economic and demographic characteristics and information and communication technology characteristics of the municipality were considered as control variables. The data refer to the year 2019. Propensity Score Matching was used as an analysis technique, a statistical method that allowed estimates to be obtained about the impact of adopting NFSe by comparing groups of municipalities that adopted it and those that did not. The main results obtained are that the adoption of the NFSe optimized not only the ISS collection, but also that of other municipal taxes, showing a spillover effect. Furthermore, the NFSe had a positive impact on social and economic expenses, better aligning resource allocation with local needs. ICT initiatives, represented by e-governance dimensions, have offered a positive effect on public governance, improving the efficiency and transparency of taxation and strengthening government accountability.